Manajemen Kepemimpinan Lembaga Kursus Dan Pelatihan Budi Mulia Dua Culinary School Yogyakarta Sebagai Lkp Berbasis Dunia Usaha Dan Dunia Industri - Agus Cahyono (Media Manajemen Pendidikan, 2022)
The present research was conducted in order to1) the leadership management of the course and training institutions as DUDI based LKP, 2) support factors and inhibitors, and 3) results and innovation in management of course and training institutions as DUDI based LKP in Budi Mulia culinary school yogyakarta. It is a qualitative descriptive study. The subject of this study is the society's leader, administrative staff, academic staff and instructor. Data collection techniques using interviews, observations, and documentation. Data analysis uses data collection steps, data reduction, data presentation, and deduction drawing. Data validity test using source triangulation and technical triangulation. Research results show that 1) the leadership management of the course and training of the Budi Mulia culinary school yogyakarta as DUDI based LKP consists of: A) planning by creating concepts, targets and objectives embodied in the program planning matrix, b) the organization by meeting all the stake holders involved, the work relationship between the society's staff has been in place, no one has collapsed under the organizational structure, c) execution by establishing a program according to DUDI's needs, basic competence according to DUDI's needs, infrastructure tools was closer to the DUDI’s facility, the instructor involved the active DUDI in the hotel, the monitoring and hiring information from DUDI, and d) surveillance by direct monitoring and evaluation.2) supporting management of the DUDI training program that is young, quick response, quick adaptation, and rapid adaptation of human resources, and excellent support and education from the local district foundation and education office, good partnerships with DUDI partners. While the inhibitor was the adjustment in DUDI's teaching schedule with work time, English mastery was still lacking for international communication. 3) as a result of the management of the leadership of the two courses and training groups as DUDI based LKP that this management process could run very well with the creation of research indicators.